2019
DOI: 10.3390/s19143183
|View full text |Cite
|
Sign up to set email alerts
|

Low-Power and Low-Cost Environmental IoT Electronic Nose Using Initial Action Period Measurements

Abstract: In this work, we present a complete hardware development and current consumption study of a portable electronic nose designed for the Internet-of-Things (IoT). Thanks to the technique of measuring in the initial action period, it can be reliably powered with a moderate-sized battery. The system is built around the well-known SoC (System on Chip) ESP8266EX, using low-cost electronics and standard sensors from Figaro’s TGS26xx series. This SoC, in addition to a powerful microcontroller, provides Wi-Fi connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…This pin was selected as the power input pin for the microcontroller. Weather conditions are one of the most important factors influencing the performance of solar panels [70]. According to the data we collected on the power efficiency of the solar panel connected to the end-node, the panel operates at 5.5V/338mA, 4.3V/205mA, and 4.0V/123mA for sunny, cloudy, and rainy hours, respectively.…”
Section: ) Energy Autonomy Of the Lwngmmentioning
confidence: 99%
“…This pin was selected as the power input pin for the microcontroller. Weather conditions are one of the most important factors influencing the performance of solar panels [70]. According to the data we collected on the power efficiency of the solar panel connected to the end-node, the panel operates at 5.5V/338mA, 4.3V/205mA, and 4.0V/123mA for sunny, cloudy, and rainy hours, respectively.…”
Section: ) Energy Autonomy Of the Lwngmmentioning
confidence: 99%
“…Special care [26] in the design of an electronic nose is required to provide a rapid change of sensors' exposure to different gases, remembering to ensure repeatability of measurement conditions. Szczurek et al [27] and Staymates et al [28] reported measurements in "sniffing" mode when frequent changes between studied odor and pure air occur or in the initial time of the sensors' action [29]. In Figure 3, we present another comparison of models' performance as a function of time of measurement from which data are available for model building.…”
Section: Resultsmentioning
confidence: 97%
“…The temperature sensor, GPS sensor, voltage sensor, low-power technology, and timing were employed to ensure the realisation of a series of functions [ 17 , 18 ]. The required executive modules of PZQ-delivery, malfunction alarm, video shooting, low-power control, and delivery reminder were all embedded and controlled by the central processing unit (CPU) [ 19 ]. The smart devices are fully equipped with waterproof, anti-collision, and cold-proof capabilities.…”
Section: Methodsmentioning
confidence: 99%